Haloperidol in treatment resistant schizophrenia: a case report - Ridzwan, Hijaz; Tuan Mohamad, Tengku Mohd Saifuddin (Malaysian Psychiatric Association, 2017)
A substantial percentage of patients will have an inadequate response to clozapine in treatment resistance schizophrenia. Therefore, different approaches need to be considered for managing this group of patients. We present a case of a treatment resistant schizophrenia patient who shows poor response toward clozapine. Later, he was started with haloperidol. Even though antipsychotic superiority of clozapine in relation to haloperidol is significant, this patient demonstrated otherwise